BUDIDAYA CABAI MERAH BESAR (Capsicum annuum L.) DI KABUPATEN BULUKUMBA DITINJAU DARI ASPEK KESESUAIAN LAHAN - Robbo, Anwar; Boceng, Annas; Ibrahim, Bakhtiar; Tjoneng, Amir; A, Muh. Taufiq (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2025)
Red chilli productivity is influenced by land suitability, climatic factors, and nutrient content. Various ways are done and continue to be developed to overcome land problems with actual soil conditions that are not suitable, as well as to overcome the constraints of high rainfall. The purpose of the study was to determine the actual and potential land suitability and inhibiting factors for large chilli plants in Gantarang District. The results of actual land suitability are marginal suitability (S3) with limiting factors of water availability (high rainfall) in all land units and rooting media (soil depth) in land units 4 and 7. Improvement efforts made for high rainfall are by making drainage channels, raising beds, and planting at the end of the rainy season. Improvement efforts with the limiting factor of soil depth in land units 4 and 7 are tillage on solid, soft, and thin layers. Efforts to improve soil depth require sophisticated tools and technology, and high costs.